Producing Diversity: Agroforests Sustain Avian Richness and Abundance in India's Western Ghats - Karanth, Krithi K.; Sankararaman, Vishnupriya; Dalvi, Shashank; Srivathsa, Arjun; Parameshwaran, Ravishankar; Sharma, Sushma; Robbins, Paul; Chhatre, Ashwini (Frontiers in Ecology and Evolution, 2016)
Globally, protected areas have long been the corner stone of biodiversity conservation efforts. In India’s Western Ghats, small and isolated protected areas are embedded in a matrix of multiple land-uses, most of which include agroforests. These agroforests are being increasingly recognized for their supplementary role in conserving wildlife. We examined bird species richness and densities in areca (Areca catechu), coffee (Coffea arabica and Coffea canephora) and rubber (Hevea brasiliensis) agroforests in the Western Ghats. We developed a priori hypotheses, predicting that bird species richness and guild density would be highest in coffee, followed by areca and rubber agroforests. We carried out 551 point-count surveys involving 386 hours of sampling in 187 agroforests across a 29,634 km2 area of the Ghats. We observed 204 bird species, of which 170 were residents. The average estimated richness per agroforest was higher in coffee (60.5) compared to rubber (45.4) and areca (34.1). We modeled species richness as a function of relevant biogeographic and environmental covariates. The most influential factors were tree cover, tree density and rainfall in all agroforests, but the strength of these effects varied. Coffee supported higher densities in all four habitat and three feeding guilds compared to areca and rubber. We integrated extensive field sampling with modeling that accounted for imperfect detection, while assessing bird richness and densities across multiple agroforest types. We establish that coffee agroforests are substantially richer in birds than rubber and areca, but all three agroforests play an important role in providing subsidiary habitats for birds in the Ghats. Policy decisions and markets must incorporate such biodiversity values and services provided by these agroforests to sustain and facilitate long-term biodiversity conservation.